(untitled) (One Health & Risk Management, 2023)
Introduction. Mortality among tuberculosis patients, both nationally and globally, has decreased significantly in the last 10 years, but the current epidemiological situation in tuberculosis allows to predict a new rise in the endemic state of the disease due to the increase of TB/HIV coinfection and the resistant tuberculosis. Material and methods. The patient’s reports were analyzed – new cases, deaths due to the progression of tuberculosis registered in the Municipal Clinical Hospital of Phthisiopneumology, Chisinau, in 2 periods: the 1st period – 2001-2003 and the 2nd period – 2018-2020. During both periods, 64 new cases died in the hospital due to the progression of tuberculosis. Statistical data processing was performed with the application of the Student (t) test, the data were considered statistically true when p<0.05. Results. In the first period, the age between 25-54 years (81.3%) predominated, in the second period between 45-65+ (73.5%) years of the deceased patients. In both periods, a high share of unemployed patients was found. In the 2nd period compared to the 1st period a severe form of disseminated tuberculosis was established – generalized tuberculosis that was not registered in the first period, the number of deaths with TB/HIV increased 6 times, 4.5 times – with stomach resection in anamnesis, 2 times – with diabetes, 1.5 times with chronic alcoholism. Primary multidrug-resistant tuberculosis was confirmed at 21.9%, extensively resistant tuberculosis – at 4.7% of deceased patients. Conclusions. In the second period, the majority of the patients new cases due to the progression of tuberculosis died of severe forms of tuberculosis – generalized, increased number of comorbidities (mainly HIV infection), the presence of a large number of cases with primary resistant tuberculosis.